High-power 50-MHz source of waveform-stable, multi-octave infrared pulses - Butler, Thomas P.; Xu, Jia; Lilienfein, Nikolai; Nagl, Nathalie; Gerz, Daniel; Hofer, Christina; Gaida, Christian; Heuermann, Tobias; Gebhardt, Martin; Fischer, Marc; Holzwarth, Ronald; Mei, Michael; et al. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Waveform-stable, pulsed laser sources have enabled both time-domain and frequency-domain precision metrology, through real-time measurement of electric-field-driven light-matter interactions on their native femto- and attosecond time scales, and by harnessing the frequency-comb nature of high-repetition-rate pulse trains. Particular interest has been shown in these sources for use in infrared (IR) molecular fingerprinting [1,2], offering increased sensitivity and specificity compared to traditional, thermal-source-based Fourier-transform spectroscopy, for applications such as biomedical spectroscopy or trace-chemical sensing. Here, we present a compact, 50-MHz source of high-power, waveform-stable IR pulses. Driven by a 2μm based fiber chirped pulse amplifier (FCPA), three parallel nonlinear fiber channels are used to cover the spectral range of 1.4 to 20 μm.
CRIS-Team Scopus Importer:2023-04-20